Quantification and Detoxification of Aflatoxin in Food Items: Aflatoxin Detoxification in Food Items - Nisa, Alim-un-; Zahra, Naseem; Hina, Sajila; Hayat, Rizwan; Ejaz, Nusrat (Biological Sciences - PJSIR, 2013)